Effect of Partial Replacement of Zn with Cd on Optical Properties of Zinc Thiourea Chloride (ZTC) Crystal. (2016) - Muley, Gajanan G.; Ambhore, Prakash S.; Naik, Anil B.; Gambhire, Anil B.
Abstract: Good quality crystals of pure and Cd doped zinc thiourea chloride (ZTC) were grown by low temperature solution growth method for second harmonic generation (SHG) applications. The effect of Zn replacement with Cd in ZTC crystals on optical properties has been studied by ultraviolet-visible spectroscopy. The improvement in the optical transparency and SHG efficiency of ZTC crystals with Cd dopants has been confirmed. The doping with Cd cannot modify lower cutoff wavelength. The powder X-ray diffraction analysis of the grown crystals has also been presented.